Influence of Helicobacter pylori Infection on Atherosclerosis Risk Factors in Older People - Zefenkey, Zean (Science Journal of University of Zakho, 2022)
Atherosclerosis is a significant cause of mortality from cardiovascular disease. The role of Helicobacter pylori (H. pylori) infection in atherogenesis is debatable. The current study aimed to assess the association between H. pylori infection and some risk factors of atherosclerosis in older people. 180 males and females, apparently healthy, over 60 years old, were examined by Fecal Helicobacter Pylori-Antigen ELISA test for H. pylori infection. Blood pressure, high-density lipoprotein-cholesterol (HDL-cholesterol), low-density lipoprotein-cholesterol (LDL-cholesterol), triglyceride (TG), fasting blood glucose, and body mass index (BMI) were measured for all participants.The faecal H. pylori antigen-positive group had a lower HDL-cholesterol level and higher levels of LDL-cholesterol, triglyceride, fasting blood glucose, and BMI than the faecal H. pylori antigen-negative group with a statistical difference (P < 0.05). The faecal H. pylori antigen-positive group had 2.4, 2.2, 2.6, 2.5 fold more likely to have increasing in the LDL-cholesterol, triglyceride, BMI, and decreasing in HDL-cholesterol, respectively. This risk became more considerable after adjustment for gender, age, blood pressure, and fasting blood glucose (adjusted odds ratio (AOR)= 3.1, 3.0, 3.3, 3.3), respectively.The infection by H. pylori in older adults is an independent factor for increasing lipid profile and BMI, which are the key modifying factors for the progress of atherosclerosis.
Keywords: Helicobacter pylori; atherosclerosis; older people; cardiovascular diseases; faecal H. pylori antigen test